2020
DOI: 10.3390/ijerph17134801
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age on Partial Clinical Remission among Children with Newly Diagnosed Type 1 Diabetes

Abstract: Partial clinical remission (PCR) is a transitory period characterized by the residual endogenous insulin secretion following type 1 diabetes (T1D) diagnosis and introducing the insulin therapy. Scientific interest in PCR has been recently increasing, as this phase could be crucial to preserve functional beta cells after T1D onset, also taking advantage of new therapeutic opportunities. The aim of this study was to assess the frequency, duration and associated factors of PCR in children newly diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 41 publications
6
14
1
4
Order By: Relevance
“…In our bivariate analysis, only the lower insulin dose at T1D onset could predict remission. Although not significant, and according to previous data, we found that patients with higher BMI and older age at diagnosis are more prone to experience remission ( 69 ). In general, children experience remission to a higher extend than adults, and within the first group, the probability of remaining in remission is greater as the onset age increased ( 70 ).…”
Section: Discussionsupporting
confidence: 78%
“…In our bivariate analysis, only the lower insulin dose at T1D onset could predict remission. Although not significant, and according to previous data, we found that patients with higher BMI and older age at diagnosis are more prone to experience remission ( 69 ). In general, children experience remission to a higher extend than adults, and within the first group, the probability of remaining in remission is greater as the onset age increased ( 70 ).…”
Section: Discussionsupporting
confidence: 78%
“…Those who were diagnosed at a younger age had a lower HbA1c at diagnosis but had higher HbA1c from 3 months post‐diagnosis to 10 months post‐diagnosis. In part, some of this can be associated with the increased rate of partial clinical remission in children diagnosed at an older age 21,22 . Children who were diagnosed at a younger age were more likely to use insulin pumps, which is consistent with previous studies 23–26 .…”
Section: Discussionsupporting
confidence: 85%
“…However, this period is very important to determine future glycemic control and to set habits, beliefs as long as fears (2). Current data suggest that chronically high glucose levels may impair insulin synthesis/ secretion, beta cells survival and insulin sensitivity, therefore improving blood glucose (BG) control is the most important step for preserving pancreatic beta cells (3,4).…”
Section: Introductionmentioning
confidence: 99%